Gut Microbiota Correlates With Clinical Responsiveness to Erythropoietin in Hemodialysis Patients With Anemia - Yifan Zhu; Yuyan Tang; Haidong He; Ping Hu; Weiqian Sun; Meiping Jin; Lishun Wang; Xudong Xu (Frontiers in Cellular and Infection Microbiology, 2022)
The main treatment for renal anemia in end-stage renal disease (ESRD) patients on hemodialysis is erythropoiesis (EPO). EPO hyporesponsiveness (EH) in dialysis patients is a common clinical problem, which is poorly understood. Recent searches reported that gut microbiota was closely related to the occurrence and development of ESRD. This study aims to explore the changes in gut microbiota between ESRD patients with different responsiveness to EPO treatment. We compared the gut microbiota from 44 poor-response (PR) and 48 good-response (GR) hemodialysis patients treated with EPO using 16S rDNA sequencing analysis. The results showed that PR patients displayed a characteristic composition of the gut microbiome that clearly differed from that of GR patients. Nine genera (Neisseria, Streptococcus, Porphyromonas, Fusobacterium, Prevotella_7, Rothia, Leptotrichia, Prevotella, Actinomyces) we identified by Lasso regression and ROC curves could excellently predict EH. In contrast, five genera (Faecalibacterium, Citrobacter, Bifidobacterium, Escherichia–Shigella, Bacteroides) identified by the same means presented a protective effect against EH. Analyzing the correlation between these biomarkers and clinical indicators, we found that gut microbiota may affect response to EPO through nutritional status and parathyroid function. These findings suggest that gut microbiota is altered in hemodialysis patients with EH, giving new clues to the pathogenesis of renal anemia.